Analisis Strategi Bersaing dalam Persaingan Usaha Penerbangan Komersial - KUNTJOROADI, Wibowo; Safitri, Nurul (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The aim of this research is to analyze the implementation of Sustainable Competitive Advantage (SCA) as a strategy taken by PT Garuda Indonesia in facing the commercial flight business competition in Indonesia. This research adopted Boston Consulting Group (BCG) matrix theory and the SCA approach to identify the competitive position of Garuda among its competitors in the airline industry and to analyze the component of competitors, consisting familiarity towards its own product, familiarity towards competitors, familiarity towards the competitors’ product and the component of competition techniques comprising cost advantage, product differentiation, market focus, pioneering products and market synergy. The result of this research shows that competitive position of Garuda in the airline industry in Indonesia is in the star quadrant, possessing the growth of long run opportunities. The strategies that could be adopted were forward integration, backward integration, horizontal integration, market penetration, market development and product development. Therefore it could be concluded that the SCA concept could be adopted as the marketing strategy of Garuda. The optimal adoption of the SCA concept as the marketing strategy that possessed the sustainable competition requires mending and improvement of such strategies as market synergy, human resources development and the market extension.